PERAN DAN KEKUATAN PEMBUKTIAN KETERANGAN AHLI BAGI TERDAKWA YANG SEDANG MENJALANI PEMULIHAN MEDIS (PUTUSAN NOMOR 1050/PID.SUS/2022/PN DPS): The Role and Evidentiary Strenght of Expert Testimony for Defendants Undergoing Medical Recovery (Court Decision No.1050/Pid.Sus/2022/PN Dps) - Syahran Meizar Abdullah; Wangga, Maria Silvya Elisabeth (Faculty of Law, Universitas Trisakti, 2026)
Narcotics abuse is a complex legal problem because on the one hand it is seen as a criminal act, but on the other hand, narcotics can also be used for medical recovery purposes as regulated in Law Number 35 of 2009 concerning Narcotics. The difference between the use of narcotics in the context of medical recovery and the illegal abuse of narcotics often does not receive adequate attention in judicial practice, especially in the evidentiary mechanism in trial. The formulation of the problem raised in this study is